Simulation and inference for stochastic processes with YUIMA : a comprehensive R framework for SDEs and other stochastic processes /: a comprehensive R framework for SDEs and other stochastic processes. (2018) - Iacus, Stefano M (Stefano Maria); Yoshida, Nakahiro
No abstract available